FDS Results for Selecting the Right Scenario in the Case of a Building Fire: A Case Study - Florin Manea; Emilian Ghicioi; Marius Cornel Suvar; Maria Prodan; Nicolae Ioan Vlasin; Niculina Sonia Suvar; Titus Vlase (Fire, 2022)
On the evening of 5 April 2014, at a building located on 122 Tomis Boulevard, Constanta Municipality, Constanta County, Romania, a restaurant with its kitchen on the ground floor and a lounge bar located on the first floor experienced a fire, one that resulted in four victims and total building destruction. An important step in the technical-scientific expertise was the investigation of the incident based on the elaboration of two fire scenarios using the Fire Dynamic Simulator (FDS) model, which observed the fire propagation, the generation of toxic gases (carbon monoxide that disoriented and intoxicated the victims, three of whom could not save themselves) depending on the location of the plausible ignition sources, and explained the destructive effects. This paper focuses on the steps required to identify the critical conditions that led to the occurrence of the unwanted event. Based on the calculations, hypothesis, and FDS simulations, the mechanism of the event occurrence was considered to be strongly related to the onsite observations and criminal file issued by the state authorities.